Multi National Corporations, Development Discontent and Civil Society The Pathology of People's Movement against Coca Cola in India - K. R. Lakhsmy Devi
The emergence of globalisation along with liberalisation and privatisation has led to a situation hitherto unprecedented in the history of developing countries. The Structural Adjustment Programmes (SAP) undertaken by many of these countries, not only opened up their economies, but pulled them to the vortex of the `global system' as never before. One of the immediate manifestations of the economic reforms in the developing countries was a manifold increase in the presence of Multi National Corporations (MNCs) who were powered by the fundamental capitalist concept of profit. Two things can happen when an external agency like a MNC intervenes in a local area and community. One, the external agency simply overlooks the local interests and local initiatives and two it shows a lack of vision and understanding of the dynamics of the locality and community. Moreover, these MNCs are for most part beyond the control of the localgovernments and many of them are more powerful than the local governments. The enormous power of these MNCs, their fragmented loyalties, their essential non accountability to the larger public and the abundant examples of many corporate mischieves make them suspicious in the eyes of many in the civil society. The Governments, anxious to have foreign direct investment, are pushed to the bottom line. In this process, the human, social, environmental and cultural rights of the civil society are violated. In such a context, civil society has no option rather than to rise and revolt. The peoples movement against Coca Cola in India is a typical example of civil society's revolt against corporate intervention in civil rights